Outsourcing Mental Health Programs: Harms to Public Education and to Students - Janzen, Melanie D.; Mayor, Christine; Sanni-Annibire, Hafizat (Canadian Journal of Education / Revue canadienne de l'éducation)

(untitled) (Canadian Society for the Study of Education, 2025)
Students are experiencing high levels of stress and mental health distress and are at greater risk of suicide, resulting in calls to provide appropriate mental health supports in schools. In response, provincial governments are outsourcing K–12 mental health supports to private organizations (both non- and for-profit). Through a review of Manitoba education documents, we traced over 50 private organizations recommended by the provincial government and over $8.9 million of public money spent on these programs. Situated within the broader neo-liberal trend of the privatization of public education, we then used a critical policy analysis approach to analyze these programs’ content, explicating the ways in which these outsourced programs endorse the deprofessionalization of the teacher and the self-responsibilization of students while enlisting problematic content. We argue that outsourcing ultimately undermines education as a public good and recommend holding governments accountable, developing research-informed mental health supports, and implementing a critical assessment process when considering outsourcing to private organizations.